2002
DOI: 10.1159/000057999
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Peanut Allergen Ara h 3: Effects on IgE Binding and T Cell Stimulation

Abstract: Background: Peanut allergy is a major health concern due to the increased prevalence, potential severity, and chronicity of the reaction. The cDNA encoding a third peanut allergen, Ara h 3, has been previously cloned and characterized. Mutational analysis of the Ara h 3 IgE-binding epitopes with synthetic peptides revealed that single amino acid changes at critical residues could diminish IgE binding. Methods: Specific oligonucleotides were used in polymerase chain reactions to modify the cDNA encoding Ara h 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 16 publications
1
55
1
Order By: Relevance
“…[27, 28]]. But again, in contrast to our study, often more than one amino acid per linear epitope was exchanged, and in most cases, many different amino acids were mutated in each molecule.…”
Section: Discussioncontrasting
confidence: 59%
“…[27, 28]]. But again, in contrast to our study, often more than one amino acid per linear epitope was exchanged, and in most cases, many different amino acids were mutated in each molecule.…”
Section: Discussioncontrasting
confidence: 59%
“…Similar attributes have been engineered into peanut allergen Ara h 3 [32]. Since there are three major peanut allergens (Ara h 1, Ara h 2, and Ara h 3) [33], it seems likely that it will be possible to produce hypoallergenic forms of all three allergens, and, when coupled with an appropriate adjuvant, be a potentially safe, effective treatment for peanut allergy.…”
Section: Discussionmentioning
confidence: 99%
“…This was performed for the peanut allergens Ara h 1, 2, and 3. Twenty three IgE-binding regions were found for the 63kDa Ara h 1 [23,24], 10 for the 17 kDa Ara h 2 [25], and only four for the 50 kDa Ara h 3 [26]. It was found that single amino acid substitutions in the peptides could remove most IgE-binding activity [23,24].…”
Section: Engineering Out Ige-binding Sequencesmentioning
confidence: 97%